The Journal of the Earl of Egmont Abstract of the Trustees Proceedings for Establishing the Colony of Georgia, 1732-1738 - Caldwell, Lee (Wormsloe Foundation Publication, 1962)
The Journal of the Earl of Egmont reveals private historical records kept by John Perceval, the first Earl of Egmont and secretary for the Common Council, a council appointed by the Charter of the colony of Georgia. A close friend of James Edward Oglethorpe, Egmont was instrumental in various colonial projects, including obtaining money for the new Carolina charter, serving as the first president of the Trustees, and often serving as the chairman of the Common Council. His careful records and plentiful writing found here offer a historical perspective on Georgia's early days. The Georgia Open History Library has been made possible in part by a major grant from the National Endowment for the Humanities: Democracy demands wisdom. Any views, findings, conclusions, or recommendations expressed in this collection, do not necessarily represent those of the National Endowment for the Humanities.